Optimisme Remaja yang Tinggal di Panti Asuhan Ditinjau dari Kebersyukuran dan Konsep Diri - Wahid, Adi Winarni; Larasati, Ageng; Ayuni, Ayuni; Nashori, Fuad (HUMANITAS, 2018)
Most of teenager who live in orphanage might experience lack of self-fulfillment in both physical and psychological needs that impact on their optimism. There are some factors that influence on optimism, those are: gratefulness and self-concept. This research aims to find the effect of gratefulness and self-concept to optimism of teenager who live in orphanage. 243 teenagers who live in 9 orphanages in Sleman, Yogyakarta were involved as subjects. Data were collected through Optimism Life Orientation Test Revised (LOT-R), gratefulness scale and Tennessee Self Concept Scale (TSCS). Data were analyzed using multiple linear regressions which were computed through Statistical Product and Service Solution (SPSS) for windows release 22,0. The results showed that gratefulness and self-concept effect on optimism.  Gratefulness and positive self-concept allow teenager to be more aware to their competencies which encourage them to improve their capability as well as their skills that in turn leads to the higher optimism.